FPGA Implementation of a Novel Oversampling Deadbeat Controller for PMSM Drives - Rovere, Luca; Formentini, Andrea; Zanchetta, Pericle (IEEE transactions on industrial electronics (1982), 2019)
This paper presents a novel oversampling deadbeat current control approach for permanent magnet synchronous motor drives capable of operating at a controller sampling frequency multiple of the power converter switching frequency. Model-based controllers suffer from heavy computational demand and performance degradation due to parameter uncertainties. The proposed controller concurrently with field-programmable gate array implementation permits to achieve a constant switching frequency and an optimal current ripple along with a high current-loop bandwidth and robust behavior to parameter variation. A disturbance observer has been added to the proposed controller in order to compensate for the converter voltage distortions. The proposed control strategy is tested through both simulations and experiments.